Analysis of Obstacles and Obstacles to the Use of Digital Money in Society - Rosalinda Sihombing; Putri Wahyu Harahap; Selma Bintang Afrizalia; Mailen Kristina Zebua; Hildawati Hildawati (Journal of Economics and Social Sciences (JESS), 2026)
This research aims to analyze the obstacles and obstacles in the use of digital money in society. The research focus includes network and transaction constraints, administrative costs and transaction deductions, security issues, the level of public trust in digital systems, and assistance and problem handling services. This study uses a descriptive quantitative method with data collection techniques through the distribution of questionnaires to 45 respondents using digital money. Data analysis techniques were carried out using descriptive analysis through tables, percentages, charts, and interval scale scores. The results showed that all aspects of the research were in the agree category, which means that respondents still felt various obstacles in the use of digital money. Administration fees and transaction discounts are the most dominant obstacles with the highest interval score of 180. In addition, security issues such as fraud and account hijacking as well as the level of public trust in digital systems also received a high score of 177. This study concludes that aspects of cost, security, and service quality are still important factors that affect people's comfort and trust in using digital money.